Prevalence of Occupational Injuries in selected Coir Industries in Sri Lanka: a cross-sectional study - Onni, Anindita Tasnim; Dodanwalage , Asela Kumar Perera; Bråtveit, Magne; Moen, Bente Elisabeth (International Journal of Occupational Safety and Health, 2023)
Introduction: The coir industry processes fibers from coconuts and is important for a high number of people in Sri Lanka. Coir workers handle several dangerous machines. This project has studied occupational injuries among coir workers. Methods: This cross-sectional study was performed in six medium-sized coir industries in Sri Lanka, each with 15-100 employees. The workers who were present at work on the two days the researchers visited the respective industries (128 of total 214 workers) were interviewed on socio-demographics, work tasks they normally perform and occupational injuries they had experienced in the last three months. Independent T-tests and Chi-square tests were used to analyze for differences between groups. Results: The mean age of the 128 interviewed workers was 45 years and 53.9% were male. Totally 34 (26.6%) of the workers had experienced at least one injury each during the past three months. Women reported significantly more injuries than men (38.9% vs 15.9%). The workers operating machines reported significantly more injuries than workers who performed other types of work (42.3% vs 22.0%). Slipped, tripped, and fall (64%) were the most common events of injury seen among the injured workers followed by cuts by sharp objects or machines (20%). The most common type of injury among the workers reporting injuries were cuts and bruises (50%). Conclusion: More than one-fourth of the workers reported to have been injured in the last three months, indicating a high injury risk. This raises concerns and highlights the need for preventative measures to minimize risks.